2019
DOI: 10.5194/bg-16-1641-2019
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the soil N<sub>2</sub>O emission intensity of croplands in northwest Europe

Abstract: Abstract. The application of nitrogenous fertilisers to agricultural soils is a major source of anthropogenic N2O emissions. Reducing the nitrogen (N) footprint of agriculture is a global challenge that depends, among other things, on our ability to quantify the N2O emission intensity of the world's most widespread and productive agricultural systems. In this context, biogeochemistry (BGC) models are widely used to estimate soil N2O emissions in agroecosystems. The choice of spatial scale is crucial because la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Schäfer et al [151] reported higher N 2 O emissions measured by closed chambers than by micrometeorological field-scale methods. In addition, when N 2 O emissions are measured at the hourly time step and at small spatial scale and then upscaled to the daily time step and the field scale, N 2 O fluxes may be overestimated [119,151].…”
Section: Types Of Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Schäfer et al [151] reported higher N 2 O emissions measured by closed chambers than by micrometeorological field-scale methods. In addition, when N 2 O emissions are measured at the hourly time step and at small spatial scale and then upscaled to the daily time step and the field scale, N 2 O fluxes may be overestimated [119,151].…”
Section: Types Of Measurementmentioning
confidence: 99%
“…Different types of field observations (e.g., soil moisture, soil temperature, soil NO 3 − and crop yields) should be compared with simulated values to improve model performance for simulating the N-cycle and N 2 O emissions [180,182]. In addition, the measurement of N 2 O emissions (e.g., length of measurements, applied method for N 2 O measurement and the scales) also influence the evaluation of model performance [119,185].…”
Section: Denitrification Processesmentioning
confidence: 99%
“…The highest EF for leguminous crops indicates that the management of fertilisation for these crops, or for the rotation itself, can be improved on the input data. Finally, information about crop-specific EF turns to be useful to design crop successions and compiling emission inventories (Myrgiotis et al, 2019). However, our results were higher than the 1 % default value defined by the IPCC guidelines for the N applied to agricultural soils, mainly because we consider only the N applied as fertiliser, neglecting animal excretions, crop residues, deposition, mineralization and fixation.…”
Section: Effect Of Climate On N2o and Ch4 Emissionsmentioning
confidence: 75%
“…Experts agree that N 2 O soil emissions are site-specific and have high spatial and temporal variability (Osborne et al 2010;Smith 2017;Snyder et al 2009). Additionally, available models still have high levels of uncertainty in estimating N 2 O fluxes (Myrgiotis et al 2019), and inconsistencies between laboratory simulations and field measurements have been reported (Jarecki et al 2009). Such level of environmental variability, together with yet partial knowledge of the N-cycle dynamics, makes it difficult to clearly identify cause-effect mechanisms between cover crops and N 2 O fluxes (Venterea et al 2012).…”
Section: Nitrous Oxide Contribution To Agricultural Greenhouse Gas Emissionsmentioning
confidence: 99%